The effectiveness of imagery and coping strategies in sport performance - Omar Fauzee, Mohd Sofian; Wan Daud, Wan Rezawana; Abdullah, Rahim; Abd Rashid, Salleh (EuroJournals, 2009)

(untitled)
The present study investigated the effectiveness of imagery and coping strategies in sport performance. Participants were 106 person, both male (n=42) and female (n=64) aged between 17 and 45 years old who represented the different level of participants of sport. Which is State players (n=46), National players (n=38) and District/university players (n=22) in various sports competitions. Participants completed the SIQ questionnaires to measure imagery skill while using ACSI-28 questionnaires to measure coping skill. Result showed Malay respondents is the higher interested in the study are 79 persons. Meanwhile, sports involved of respondents are others sport (archery, football/futsal, netball, rugby, hockey and athletics) which are 50%. The most level of age participated are 21 to 24 years old. Most probably, in this age level, some of them represented for national (n=38) and state (n=46). The result of this study showed that the SIQ and ACSI-28 is reliable to the respondents participated which is the Cronbach's alpha coefficients, mean and standard deviation of all the variables are presented were .932. For the ACSI-28, the participants most frequently used coping skills is the confidence (M=2.0802, SD=.5644) and the least frequently used is coachability (M=1.5519, SD=.4361). From the resulted, there were significant differences in one subscales of ACSI-28 coping with adversity between male and female, which are concentrated with t (106) = 2.118, p = .037. One Way ANOVA analysis subscales with level of participants result showed that all subscales imagery (SIQ) were significant differences with levels of participation. In addition five subscales ACSI-28 also were significant differences with level of participations in this study. It might be because of the participated from a national and state player (n=38, n=46). In addition, result showed only subscales coping with diversity are significant differences where p=.037 (M=2.0448, SD=.5115) compare the rest of subscales ACSI-28.